PENGARUH TEKANAN STAKEHOLDER DAN CORPORATE GOVERNANCE TERHADAP KUALITAS SUSTAINABILITY REPORT - Rini Suharyani; Ihyaul Ulum; Ahmad Waluyo Jati (Universitas Muhammadiyah Malang, 2019)
The purpose of this study is to examine the effect of stakeholder pressure and corporate governance on the sustainability report quality in the companies listed on the Indonesia Stock Exchange for 2017. The research sample numbered 28 with purposive sampling technique. Data collection techniques with secondary data. Data is taken in the form of published data on the official website of the companies. Data analysis uses Content Analysis and WarpPLS 6.0. Based on the results of the study found stakeholder pressure have a significance positive effect on the sustainability report quality and corporate governance have a significance positive effect on the sustainability report quality. Keywords: Sustainability Report, Stakeholder Pressure, Corporate Governance